Cádmio e silício na fisiologia e bioquímica de Enterolobium contortisiliquum (Vell.) morong em cultivo hidropônico - Senhor, Daiane Franchesca (2021)
Heavy metals are among the main pollutant sources generating serious environmental problems. Among these elements, we highlight cadmium (Cd), a highly toxic element that is easily absorbed by plants. Enterolobium contortisiliquum (Vell.) Morong is a tree species with a wide distribution in Brazil and is recommended for reforestation and recovery of degraded areas. Besides the good choice of plant species, the use of beneficial elements to help these plants to develop in these hostile environments is of fundamental importance. In this sense, silicon (Si) helps the development of several plant species in stress situations. This study was carried out with seedlings of the species E. contorstisiliquum in a hydroponic system and divided into three chapters. The objective was to determine the sensitivity or tolerance to Cd and the potential of Si to alleviate Cd toxicity in E. contorstisiliquum plants. In the three chapters was to evaluate the growth, photosynthesis and biochemical variables of the seedlings, being in Chapter I with the presence of Cd, in Chapter II with Si and in Chapter III with Cd and Si. The experiments were carried out in the Plant Physiology and Plant Nutrition Laboratories and in the greenhouse of the Biology Department of the Federal University of Santa Maria/RS. The seedlings were obtained in commercial substrate and after reaching 10 cm of height were transferred to the hydroponic system, where they underwent an acclimatization period only in complete nutrient solution. The trials were composed of the following treatments: the first by Cd (ClCd2) concentrations 0, 25, 50, 75 and 100μM, where the plants were exposed for 10 days to the treatments; the second by Si (Na2SiO4) concentrations: 0; 1.5; 3.0; 4.5 and 6 mM, with an exposure period of 15 days, and the third composed of Si and Cd concentrations: 1st 0mM Si + 0μM Cd; 2nd 1.5mM Si + 0μM Cd; 3rd 3.0mM Si + 0μM of Cd; 4th 1.5mM Si + 100μM Cd; 5th 3.0mM Si + 100μM Cd; 6th 0mM Si + 100μM Cd, with 15 days of exposure. All these treatments were added to the complete nutrient solution. The experiments were in entirely randomized design, composed of four repetitions for each treatment and at the end of the exposure period physiological, morphological and biochemical analyses were performed. The data were submitted to variance analysis and the means were differentiated by Tukey's test at 5% probability of error. The results indicated that high concentrations of Cd, as well as Si, negatively affected the development of timbaúva seedlings, however they showed a good tolerance up to 50μM of Cd and low concentrations of Si increased the development of the seedlings. In the simultaneous use of Si+Cd, Si proved to be able to mitigate some damage caused by Cd, favoring the photosynthetic activity, the increase of total chlorophylls and decrease in lipid peroxidation of the shoot of E. contortisiliquum seedlings. Therefore, timbaúva presents a tolerance to Cd, demonstrating potential to be used in the recovery of degraded areas, and Si, as it helped in important variables, demonstrated its beneficial role.